Extracellular vesicle‐bound DNA in urine is indicative of kidney allograft injury. Issue 9 (23rd September 2022) - Sedej, Ivana; Štalekar, Maja; Tušek Žnidarič, Magda; Goričar, Katja; Kojc, Nika; Kogovšek, Polona; Dolžan, Vita; Arnol, Miha; Lenassi, Metka
Abstract: Extracellular vesicle‐bound DNA (evDNA) is an understudied extracellular vesicle (EV) cargo, particularly in cancer‐unrelated research. Although evDNA has been detected in urine, little is known about its characteristics, localization, and biomarker potential for kidney pathologies. To address this, we enriched EVs from urine of well‐characterized kidney transplant recipients undergoing allograft biopsy, characterized their evDNA and its association to allograft injury. The SEC‐based method enriched pure EVs from urine of kidney transplant recipients, regardless of the allograft injury. Urinary evDNA represented up to 29.2 ± 8% (mean ± SD) of cell‐free DNA (cfDNA) and correlated with cfDNA in several characteristics but was less fragmented ( P < 0.001). Importantly, using DNase treatment and immunogold labelling TEM, we demonstrated that evDNA was bound to the surface of urinary EVs. Normalised evDNA yield ( P = 0.042) and evDNA copy number ( P = 0.027) significantly differed between patients with normal histology, rejection injury and non‐rejection injury, the later groups having significantly larger uEVs (mean diameter, P = 0.045) and more DNA bound per uEV. ddDNA is detectable in uEV samples of kidney allograft recipients, but its quantity is highly variable. In a proof‐of‐principle study, several evDNA characteristics correlated with clinical and histological parameters ( P = 0.040), supporting that the potential of evDNA as a biomarker for kidney allograft injury should be further investigated.